Reductive Deuteration of Aromatic Esters for the Synthesis of α,α-Dideuterio Benzyl Alcohols Using D2O as Deuterium Source - Luo, Shihui; Weng, Chaoqun; Ding, Yuxuan; Ling, Chen; Szostak, Michal; Ma, Xiaodong; An, Jie (Synlett, 2020)
α,α-Dideuterio benzyl alcohols are important building blocks for the synthesis of deuterium-labeled medicines and agrochemicals. We have developed the first general single-electron transfer reductive deuteration of readily commercially available aromatic esters for the synthesis of α,α-dideuterio benzyl alcohols using benign D2O and a mild single-electron donor SmI2. This operationally convenient method features very good functional group tolerance and high deuterium incorporations (>95% D2). The potential impact has been exemplified by the synthesis of numerous deuterium labeled building blocks of important bioactive compounds. Most crucially, the method represents the first example of selective reductive deuteration of benzylic-type ketyl radicals using mild and highly chemoselective lanthanide(II) reagents.
Keywords: reductive deuteration; α,α-dideuterio benzyl alcohol; single-electron transfer; reduction; D2O